Alarm Sensor Temperatur Untuk Ruang Pendingin Menggunakan IoT - Kevin Christian; Silvia Rostianingsih; Resmana Lim (Jurnal Infra, 2022)
Technological advances are so fast that all activities use computers, making it easier for users to carry out daily activities. With conditions that are increasingly advanced and developing so that the idea is created to connect hardware and software technology that helps in the daily activities of the wider community. Currently, many raw materials and food ingredients are stored in the Refrigeration Room. One example of a Cooling Room is a refrigerator freezer. Refrigeration Room is widely used to store raw food ingredients.For this reason, to make it easier to monitor the temperature in the Cooling Room, an Android Application that is connected using IoT is made with a Temperature Sensor in the Cooling Room.The test results show that the process of monitoring the Cooling Room through IoT and Android Applications can be done easily and quickly with accurate results.